PANDANGAN HOLISTIK : MENGGALI HAKIKAT, TUJUAN DAN EPISTIMOLOGI PENDIDIKAN - Muhammad Afdal Rusmani; Abu Hasdi, Coil, Januar (CV. ADIBA AISHA AMIRA, 2023)
Multicultural education for the Indonesian people is part of Indonesia's cultural diversity. If managed well, it will be able to form a strong Indonesian national character. Indonesia is one of the largest multicultural countries in the world. Multicultural education has a contribution to the success of character-based education policies which can be the glue of the nation's culture. For this reason, multicultural education is something that is very important to implement in education in Indonesia because multicultural education can function as an alternative means of conflict resolution. Methodologically, this research is a type of library research. The results of this research are the nature of multiculturalism in Islamic education which functions to guide and direct humanity to be able to carry out orders or mandates from Allah, namely carrying out the task of living on earth as abdullah, who must obey every rule and will of Allah.